Diagnostic and Therapeutic Challenges of Cardiac Metastasis in Advanced Malignancies: A Case Series and Literature Review - Moath Albliwi; Aravinthan Vignarajah; Nishanthi Vigneswaramoorthy; Ayham Mohammad Hussein; Asfand Yar Cheema; Shimoli Barot; Gautam Shah (Case Reports in Oncological Medicine)
Conclusion: Cardiac metastasis should be considered in cancer patients who present with unexplained cardiac symptoms. A multidisciplinary approach, including imaging and biopsy, is crucial for accurate diagnosis. Despite aggressive treatment, the prognosis remains poor, emphasizing the need for early detection and better therapeutic strategies.